ANALISIS KESENJANGAN PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA BERDASARKAN ISO 45001:2018 DI PT X TAHUN 2022 - Fanny Azzahra Putri (2023)
The industrial era 4.0 and the new normal life Covid-19 post-pandemic life have triggered new challenges related to health and safety, thus driving the need for the adoption of an integrated OHS Management System to minimize work accidents and sustainably increase company value. In 2018, the international standardization ISO 45001:2018 was published as a replacement for OHSAS 18001:2007. PT X is a logistics company that carried out standardization based on OHSAS 18001:2007 from 2014 to 2017. PT X received input from the holding company to re-implement with reference to ISO 45001:2018. Therefore, it is necessary to assess the gap between the implementation of OHSAS 18001:2007 and the ISO 45001:2018 standard in order to find out how far the SMK3 has been implemented. A qualitative research design with a gap analysis approach is used to determine company gaps in implementing SMK3 based on OHSAS 18001 with ISO 45001:2018. Based on the results of data processing and analysis, the result was that the implementation of SMK3 at PT X was in the bad category with a percentage of 40.2% with a score of 188 out of 465. This was due to the unavailability of resources that could handle and develop OHSMS at PT X. From this data analysis it is known that the implementation of OHSMS at PT X OHSMS at PT X really needs improvement because it is very different from the ISO 45001:2018 OHSMS.